Embolisation of iatrogenic lumbar artery bleed causing psoas haematoma following elective lumbar puncture. Issue 11 (1st November 2022) - Oladeji, Emmanuel; Rati, Kuran; Rakhimova, Kamila; Day, Nigel
Abstract : The case of a female patient in her 50s presenting as a surgical emergency with abdominal pain and a positive Obraztsova's sign. Seven days prior to the presentation, a lumbar puncture (LP) had been performed to investigate severe headaches and exclude a subarachnoid haemorrhage. The patient was subsequently found to have an acute lumbar arterial bleed causing haemodynamic instability and a psoas haematoma. An emergency lumbar artery embolisation procedure was performed by the interventional radiology department in order to stabilise the bleed. The patient made a full recovery prior to discharge.